Silih Asah, Asih, Asuh: The Concept of Learner Character Building in Music Learning - Maulana, Marsel Ridky; Sukmayadi, Yudi; Gunara, Sandie (Journal of Music Science, Technology, and Industry, 2025)
Purpose: Indonesia faces the challenge of globalisation that can erode cultural identity, especially among the younger generation. Technological developments and foreign cultural influences often cause a shift in values and threaten the sustainability of local wisdom. This study confirms the urgency of revitalising local wisdom values in music education as an effort to maintain the nation's cultural identity amid global dynamics. Research methods: This paper uses a qualitative descriptive method with an in-depth literature analysis approach. Data were collected from various academic sources such as books, scientific journals, and research articles both in print and online. The analysis process was conducted systematically by reviewing, interpreting, and synthesising various perspectives found in the literature in order to gain a more comprehensive understanding of the concept of Silih Asah, Asih, Asuh in music learning. Results and discussion: The concept of Silih Asah, Silih Asih, and Silih Asuh in Sundanese culture offers a fundamental approach to character building through music learning. Silih Asah encourages intellectual strengthening and creativity through musical exploration, Silih Asih instils the value of empathy and compassion through togetherness in music, while Silih Asuh fosters mutual guidance and responsibility in the learning process. Implication: By integrating the concepts of Silih Asah, Silih Asih, and Silih Asuh in music learning, education can be a strategic means to form a generation that is intellectually intelligent, has emotional sensitivity, and moral integrity. This study confirms the urgency of revitalising local wisdom values in music education as an effort to maintain the nation's cultural identity amid global dynamics.